Assertive speech acts in Kompas.com news texts: a pragmatic Analysis - Fani Agustina Putri; Alfina Roisatul Isnaini; Neli Novita Sari; Sahril (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study examines assertive speech acts in Kompas.com news texts using a pragmatic approach grounded in Searle’s speech act theory. The research employs a descriptive qualitative method, with data drawn from a Kompas.com news article reporting the Jakarta floods. The data consist of clauses and sentences containing assertive speech acts, which were collected through documentation and analyzed based on their types and pragmatic functions. The findings reveal that assertive speech acts dominate the news text, appearing in various forms such as stating, reporting, explaining, and confirming. These speech acts function to deliver factual information, describe situational conditions, report official data, and reinforce the credibility of news reporting. The predominance of assertive speech acts reflects the informative nature of journalistic discourse and demonstrates how language is used to construct objectivity and social reality in online news media. This study contributes to pragmatic and discourse analysis research by providing insights into the role of assertive speech acts in shaping meaning and credibility in news reporting.